Pogodbena kazen v poslovni praksi - Prostor, Jerneja (Podjetje in delo, 2014)
The article deals with the problems which are arising from clauses included in a contract, containing the agreement on penalty, liquidated damages or limited compensation. It is often difficult to determine the intent of the parties that could derive from the included contractual amount that has to be paid as a consequence of the breach of the contract. Such an agreement is especially questionable in case of the contractual obligation having an international dimension, when the applicable law is the one of a common law system. Namely, the agreement on penalty clause is not admissible in common law systems. Afterwards, the Slovenian regulation on penalty clause is analysed and compared with the similar solutions, provided by autonomous legal sources.
Keywords: kršenje; odškodnina; pogodbe; pogodbeno pravo